2015
DOI: 10.1186/s12905-015-0226-x
|View full text |Cite
|
Sign up to set email alerts
|

Observational, prospective, multicentre study to evaluate the effects of counselling on the choice of combined hormonal contraceptives in Italy—the ECOS (Educational COunselling effectS) study

Abstract: BackgroundAdequate counselling on contraceptive methods can help users choose the most appropriate method. The aim of this study was to assess the effects of structured counselling provided by gynaecologists on selection of a combined hormonal contraception method.MethodsWomen aged 18–40 years (n = 1871) who were considering the use of a combined hormonal contraception method (pill, transdermal patch or vaginal ring) underwent a structured counselling session in which gynaecologists provided comprehensive info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In this study, the type of clinician and whether patients received counseling from their clinician influenced choice of prescription method, highlighting the importance of the patient-HCP relationship. In previous studies, b20% of primary care providers offered IUDs [9,10], while over 95% of OB/GYNs did [11], and patients counseled on the ease of use and administration of various methods were more likely to choose methods other than OC [12,13]. Interestingly, there were no statistical differences in the proportions of women dissuaded from using particular prescription methods based on age, race/ethnicity, or parity.…”
Section: Discussionmentioning
confidence: 84%
“…In this study, the type of clinician and whether patients received counseling from their clinician influenced choice of prescription method, highlighting the importance of the patient-HCP relationship. In previous studies, b20% of primary care providers offered IUDs [9,10], while over 95% of OB/GYNs did [11], and patients counseled on the ease of use and administration of various methods were more likely to choose methods other than OC [12,13]. Interestingly, there were no statistical differences in the proportions of women dissuaded from using particular prescription methods based on age, race/ethnicity, or parity.…”
Section: Discussionmentioning
confidence: 84%
“…(Dehlendorf et al, 2016) Counseling can also help anticipate events that often arise after starting a particular contraceptive method, place expectations according to the possible effects and reduce the demand for meeting providers after contraceptive use. (Gambera et al, 2015) However, the result fact of family planning counseling in Indonesia has not been as expected. The results of the research in Kebumen showed that 31.3% of midwives' knowledge was less about IUD contraception; 5% of them forget or don't know about the working mechanism of the IUD; 11.3% forgot about the effectiveness, side effects, complications, and duration of IUD use; 31.3% of midwives have low motivation regarding IUD contraceptive services; 40% of midwives prefer to serve injection acceptors and put up implants rather than providing an IUD for practical and easier reasons.…”
Section: Introductionmentioning
confidence: 98%
“…In the 1990s and early 2000s, the U.S. saw a dramatic increase in the number of available HCs, from the initial approvals of implantable and injectable contraceptives (referred to as long-acting reversible contraceptives, or LARC) to the introduction of the patch and the ring [3,5]. In this new context, contraceptive selection is related to convenience, cost, side effects, peer utilization, and awareness of method [6,7], and many women try more than one HC route in their lifetime [3]. Yet, studies of reasons for HC use are relatively limited, and mainly concern reasons for choosing one HC type over another in the context of family planning [6,7], as opposed to clinical indication(s) for use, and most focus on oral contraceptive use.…”
Section: Introductionmentioning
confidence: 99%
“…In this new context, contraceptive selection is related to convenience, cost, side effects, peer utilization, and awareness of method [6,7], and many women try more than one HC route in their lifetime [3]. Yet, studies of reasons for HC use are relatively limited, and mainly concern reasons for choosing one HC type over another in the context of family planning [6,7], as opposed to clinical indication(s) for use, and most focus on oral contraceptive use. Such data are especially limited for African Americans because even if included, findings are not reported stratified by race [8].…”
Section: Introductionmentioning
confidence: 99%